2015
DOI: 10.1039/c4ta06830k
|View full text |Cite
|
Sign up to set email alerts
|

Highly reduced molybdophosphate as a noble-metal-free catalyst for the reduction of chromium using formic acid as a reducing agent

Abstract: Cobalt-containing polyoxometalates exhibit catalytic performance for toxic chromium(vi) reduction using formic acid under mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…Huang et al (2012) reported about the catalytic reduction of Cr(VI) using Pd nanoparticle immobilized electrospun fiber. Other catalysts systems are: nanostructured polyamic acid (Omole et al 2011), goethite (Kim et al 2007), silica (Gienada et al 2016), Fe 0 (Alowitz and Scherer 2002), CCTCCAB 91095 (Song et al 2009), molyptic phosphate (Gong et al 2015), ATCC 33456 (Shen and Wang 1995) and Pd-supported aminoclay (AC) (Celebi et al 2016). After thorough literature survey, we could not find any report based on the AC-Ni catalyzed reduction of Cr(VI).…”
Section: Introductionmentioning
confidence: 96%
“…Huang et al (2012) reported about the catalytic reduction of Cr(VI) using Pd nanoparticle immobilized electrospun fiber. Other catalysts systems are: nanostructured polyamic acid (Omole et al 2011), goethite (Kim et al 2007), silica (Gienada et al 2016), Fe 0 (Alowitz and Scherer 2002), CCTCCAB 91095 (Song et al 2009), molyptic phosphate (Gong et al 2015), ATCC 33456 (Shen and Wang 1995) and Pd-supported aminoclay (AC) (Celebi et al 2016). After thorough literature survey, we could not find any report based on the AC-Ni catalyzed reduction of Cr(VI).…”
Section: Introductionmentioning
confidence: 96%
“…Thus, the removal of Cr VI is one of the foremost goal for environmental protection by either adsorption or reduction processes . The reduction of Cr VI to Cr III by formic acid is considered as one of the best and simplest techniques, especially in the presence of various metal nanoparticles (in particular, Pd‐based materials), as no extra pollution results in from the byproducts by following this protocol …”
Section: Resultsmentioning
confidence: 99%
“…We also compared the catalytic activities of the Co-containing hybrids {Co[P 4 O (7) (mbpy = 5,5Ј-dimethyl-2,2Ј-dipyridyl). [28] These compounds have similar components to that of hybrids 1-3. However, they show different catalytic performance for the reduction reaction.…”
Section: Catalytic Experimentsmentioning
confidence: 89%
“…Our recent study has shown that the reduced POMs represent a kind of noble metal-free catalyst for this system. [28,29] This paper describes the redox behaviours of hybrids 1-3 and their catalytic performance for the reduction of chromium(VI) in aqueous solutions using FA under a mild condition. 6 } polyhedra link each other in a manner of corner-and edge-sharing modes ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%